Perioperative fluid therapy impairs lymphatic pump function in male rats - Rebecca C. Harlow‐Adamek; Reetu Singh; Randolph H. Stewart; Cristine L. Heaps; Glen A. Laine; Charles S. Cox Jr.; Ranjeet M. Dongaonkar (Physiological Reports)
Abstract Because of its life‐saving benefits, perioperative IV fluid therapy remains a cornerstone of medical treatment. However, it also induces sustained edemagenic stress. The resulting persistent interstitial edema—excessive fluid accumulation in the interstitium—significantly delays recovery and worsens patient outcomes. Therefore, to gain a detailed understanding of the lymphatic functional consequences of perioperative fluid therapy, this study aimed to test the hypothesis that perioperative IV fluid therapy compromises lymphatic pump function within 3 days after major surgery. Following a midline laparotomy, animals received IV fluid therapy over 48 h during recovery (FLTP). Three days post‐surgery, mesenteric lymphatic vessels from FLTP and sham surgery (CTRL) animals were isolated, and lymphatic pump function was assessed in vitro. The transmural pressure‐pump flow and circumferential length‐wall tension relationships of FLTP vessels were altered—contraction frequency and normalized pump flow and active and passive wall tensions were significantly lower than CTRL. In vessels from another group of animals with surgically produced mesenteric venous hypertension to induce sustained edemagenic stress, only the pressure‐pump flow relationship was altered similarly to FLTP. These results demonstrate the detrimental effects of perioperative fluid therapy on lymphatic pumping, which is essential for restoring interstitial fluid pressure and resolving edema and inflammation.